Bariatric Surgery Prior to Index Screening Colonoscopy Is Associated With a Decreased Rate of Colorectal Adenomas in Obese Individuals. Issue 2 (February 2017) - Kedrin, Dmitriy; Gandhi, Shaan‐Chirag Chandrahas; Wolf, Molly; Roper, Jatin; Yilmaz, Omer; Corey, Kathleen; Khalili, Hamed; Stanford, Fatima Cody; Gala, Manish
Abstract : OBJECTIVES: : Obesity is an important risk factor for the development of colorectal cancer (CRC). Although the impact of bariatric surgery on CRC is conflicting, its impact on precursor lesions is unknown. The aim of this study was to determine whether bariatric surgery before index screening colonoscopy is associated with decreased development of colorectal adenomas. METHODS: : We performed a retrospective cohort study of bariatric surgery patients who had undergone index, screening colonoscopy at an academic center from 2001 to 2014. Patients who had bariatric surgery at least 1 year before index colonoscopy were compared with those who had surgery after colonoscopy, using multivariable logistic regression to control for presurgical body mass index, sex, gender, race, type of surgery, aspirin use, metformin use, smoking, and age at colonoscopy. RESULTS: : One hundred and twenty‐five obese individuals who had bariatric surgery before colonoscopy were compared with 223 individuals who had colonoscopy after surgery. Adenomatous polyps were found in 16.8% of individuals who had surgery first vs. 35.5% who had colonoscopy before bariatric surgery (unadjusted odds ratio (OR) 0.37, 95% confidence interval (CI): 0.21–0.64, P =0.0003). After multivariable adjustment, bariatric surgery before index screening colonoscopy was associated with a decreased risk of adenomas at index colonoscopy (adjusted OR 0.37, 95% CI: 0.19–0.69, P =0.002). CONCLUSIONS: : Bariatric surgery is associated with a decreased risk of colorectal adenomas in obese individuals without a family history of CRC.